2011
DOI: 10.1371/journal.pone.0020169
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Rag1−/−γc−/− Mice Support Multilineage Hematopoiesis and Are Susceptible to HIV-1 Infection via Systemic and Vaginal Routes

Abstract: Several new immunodeficient mouse models for human cell engraftment have recently been introduced that include the Rag2−/−γc−/−, NOD/SCID, NOD/SCIDγc−/− and NOD/SCIDβ2m−/− strains. Transplantation of these mice with CD34+ human hematopoietic stem cells leads to prolonged engraftment, multilineage hematopoiesis and the capacity to generate human immune responses against a variety of antigens. However, the various mouse strains used and different methods of engrafting human cells are beginning to illustrate stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…Continued genetic modifications of candidate host mice will probably enable at least some of the species-specific needs to be addressed in the future. These include the possibility of creating transgenic mice that will express species-specific human cytokines, or the use of humanized mice (mice transplanted with human haematopoietic or local tissue components) to create more human-type microenvironments -as has proved useful for certain types of normal human cells [53][54][55][56][57] . Orthotopic injections of CSCs into various target organs may also prove useful, and mimicry of natural tumour immunosurveillance mechanisms may be achievable using injections of specific immune effector cells (TABLE 2).…”
Section: Csc Assays: Strengths and Caveatsmentioning
confidence: 99%
“…Continued genetic modifications of candidate host mice will probably enable at least some of the species-specific needs to be addressed in the future. These include the possibility of creating transgenic mice that will express species-specific human cytokines, or the use of humanized mice (mice transplanted with human haematopoietic or local tissue components) to create more human-type microenvironments -as has proved useful for certain types of normal human cells [53][54][55][56][57] . Orthotopic injections of CSCs into various target organs may also prove useful, and mimicry of natural tumour immunosurveillance mechanisms may be achievable using injections of specific immune effector cells (TABLE 2).…”
Section: Csc Assays: Strengths and Caveatsmentioning
confidence: 99%
“…Although the current humanized mouse models are capable of producing human humoral and cellular immune responses to these pathogens, in general the results have been inconsistent and when they are detected the immune responses are typically weak [6,11,12]. The reasons for these findings are currently unclear, but previous studies have indicated that total human antibody concentrations are much lower in humanized mice than in humans and there may be a defect in classswitching, since IgM concentrations tend to be closer to human concentrations than for IgG [2,13]. One study attempted to immortalize human B cells after immunizing humanized mice and was only able to produce IgM monoclonal antibodies and not IgG producing cells, lending further support to the hypothesis that there is a lack of effective class-switching [14].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood was collected by tail bleed and stained with antibodies specific to either human or mouse CD45. Fluorescence-activated cell sorter (FACS) analysis was performed to determine percent peripheral blood engraftment of human cells (38,39).…”
Section: Cellsmentioning
confidence: 99%